Sacred water and water in religious ritual in the urban and suburban cults of Carthago Nova - Egea Vivancos, Alejandro (Gerión. Revista de Historia Antigua, 2013)
The archaeological discoveries and the literary sources are reviewed to establish very narrow knots between the religious life of the ancient Carthago Nova and the water. The water is present in the temples of the city either as integral element of the rituals or like an element clearly worshipped by means of different personifications or divinities. The lack of water in the city and the illnesses that it fomented the old lagoon propitiated these narrow knots.
Keywords: Water; Religion; Cult; Ritual; Healing Deities.